VIETNAM AS A POTENTIAL MEDIA IN VIET THANH NGUYEN’S NOVEL THE SYMPATHIZER (2015) - Annisa Karlina; Kurnia Ningsih; Desvalini Anwar (English Language and Literature, 2018)
The purpose of this analysis are to expose the issue ofVietnam as a potential mediaand to know the contribution of the implied author in revealing the meaning of Vietnam as a potential media. This analysis is related to the concept of Neo-colonialismby Kwame Nkrumah and Hegemony by Gramscithat is supported by the text and context based interpretation. The result of this analysis shows that America utilises Vietnam as their media of promotion which can be seen from their policy and economy intervention.